Off the deep end: Tonga's continental shelf politics - Brown Pulu, TJ (Te Ara Poutama - the Faculty of Maori and Indigenous Development, Auckland University of Technology, 2014)
Tonga had gone off the deep end. It proposed to grow its ocean territory in length by 60 nautical miles southeast and southwest. Hardly anyone knew the particulars, apart from a select group of senior bureaucrats in the Government of Tonga persevering to make it happen. The Tongan public paid closer attention to who might come into government at the November 2014 election and whether any women would get voted into parliament. Local media had spoon fed this slant to the masses which uncritically they consumed as the top news feed. Alternatively, raising awareness about continental shelf politics failed to appear on the public information menu. Why should it matter to ordinary Joe Blog Tongan scratching out a living in a distressed economy? The story unfolds that Lord Ma’afu, the Minister for Lands, Environment, Climate Change, and Natural Resources entered office after the first partial submission on the outer limits of Tonga’s continental shelf had been prepared. His predecessor Lord Tuita tabled the document for consideration at the United Nations in April of 2010. Ma’afu was tasked with overseeing a second partial submission to acquire 60 nautical miles in the Lau-Colville Ridge, which he delivered to the United Nations headquarters in New York on April 23rd 2014. It would be weighed up the following year in 2015 (United Nations, 2014). This essay prods two pressure points. Firstly, how did securing Tonga’s continental shelf further than the 200 mile exclusive economic zone relate to deep sea mining? And secondly, what prompted Fiji’s 2005 objection to the International Seabed Authority about Tonga’s sovereign declaration over the Minerva Reefs? In the current geopolitical climate, how would the Tongan state navigate the ocean currents?